2018
DOI: 10.1002/ejp.1249
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Transversus Thoracic Plane block, Parasternal block and fascial planes hydrodissection for internal mammary post thoracotomy pain syndrome

Abstract: The use of Transversus Thoracic Plane and Parasternal Blocks and fascial planes hydrodissection as a novel therapeutic approach to treat a residual post thoracotomy pain syndrome even when already treated with Pectoral Nerves Block and Serratus Plane Block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The available literature demonstrates the use of TTP blocks in breast resection surgery, subcutaneous internal cardiac defibrillator placement [10], and pericardial effusion drainage [21]. Other applications include acute pain management associated with sternal fractures [22] and chronic pain treatment for postthoracotomy internal mammary pain syndrome [12].…”
Section: Current Indications and Available Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The available literature demonstrates the use of TTP blocks in breast resection surgery, subcutaneous internal cardiac defibrillator placement [10], and pericardial effusion drainage [21]. Other applications include acute pain management associated with sternal fractures [22] and chronic pain treatment for postthoracotomy internal mammary pain syndrome [12].…”
Section: Current Indications and Available Evidencementioning
confidence: 99%
“…Piraccini et al described the use of a different parasternal block with the TTP block to treat a patient suffering from postthoracotomy internal mammary pain syndrome ten months after surgery [12]. Pecs blocks do not provide analgesia to the internal mammary region, whereas the parasternal and TTP blocks do.…”
Section: Current Indications and Available Evidencementioning
confidence: 99%
“…[ 6 7 ] TTM is also used in combination with parasternal block to treat the residual post-thoracotomy pain syndrome. [ 8 ] There has been limited literature on the combination of PECS1 with a TTM block for CIED insertion procedures. Hence, the present study was conducted to compare the analgesic efficacy of PECS1 block with combined PECS1 and TTM block in patients undergoing CIED insertion.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] The same author reported one case with right postthoracotomy pain syndrome received the hydrodissection of fascial planes in the internal mammary region with triamcinolone and ropivacaine together with a nerve block. [ 5 ] Ueshima reported that using local anesthetic into the fascial plane between the multifidus and longissimus muscles among two patients who underwent spinal surgery can improve patients' recovery. [ 6 ] Ueshima also recently reported that normal saline 10 mL between the fascia of the internal and external intercostal muscles can successfully relieve pain; however, Ueshima proposed that interfascial adhesion is the cause of pain.…”
Section: Introductionmentioning
confidence: 99%